NAİMA’NIN DİN VE TOPLUM GÖRÜŞÜ / Religion and Society According to Naima - COŞKUN, ALİ (Journal of History Culture and Art Research, 2015)
Religion and Society According to Naima Abstract This article deals with the idea of religion and society according to Naima.In the first chapter, his ideas about the Ottoman Society of 17th century in terms of static and structural sociology of religion dealt with and in this frame the notions of organic society, class and religion were examined. This chapter especially focuses on religious scholars (ulama), traders, soldiers, civilian people (reaiyyah) and Kadizadeli movement. In the second chapter, the ideas of Naimaabout the Ottoman Society in terms of dynamic and functional sociology of religion dealt with and in this frame the theory of stages and sociology of great mandealt with. Finally, the social and religious reformation aspects of Naima were examined. Naima’nın Din ve Toplum Görüşü Öz Bu makalede Naima’nın din ve toplum görüşleri özetlenmektedir. Evvela Naima’da statik ve strüktürel din sosyolojisi bakımından on yedinci yüzyıl Osmanlı toplumu ele alınmış bu kapsamda uzviyetçi toplum anlayışı ve din ile dört sınıf anlayışı ve din ele alınmıştır. Özellikle ulema, tüccar, asker ve reaya sınıfları incelenmiş Kadızadeliler hareketi üzerinde durulmuştur. İkinci olarak Naima’da dinamik ve fonksiyonel din sosyolojisi bakımından on yedinci yüzyıl Osmanlı toplumu ele alınmış bu kapsamda tavırlar nazariyesi ve büyük adam sosyolojisi incelenmiştir. Son olarak Naima’nın dini sosyal ıslahatçılık yönü üzerinde durulmuş ve sonuçla makale sonlandırılmıştır.